When thoughts will soar: a romance of the immediate future - Suttner, Bertha von; Dole, Nathan Haskell (Houghton Mifflin Company, 1914)
A mature work by the Austrian peace activist Bertha von Suttner, in which a group of people in the near future are able to introduce World Peace.
A mature work by the Austrian peace activist Bertha von Suttner, in which a group of people in the near future are able to introduce World Peace.
Also issued online.
Keywords: Pacifism. / fast / http://id.worldcat.org/fast/1050108; Future life. / fast / http://id.worldcat.org/fast/936730; Pacifism / Fiction.; Future life / Fiction. / http://id.loc.gov/authorities/subjects/sh2008103663; Fictional Work. / http://id.nlm.nih.gov/mesh/D022922; Autographs. / rbmscv / http://id.loc.gov/vocabulary/rbmscv/cv00177 / PSt; Library copies. / rbmscv / http://id.loc.gov/vocabulary/rbmscv/cv00154 / PSt; Science fiction. / lcgft / http://id.loc.gov/authorities/genreForms/gf2014026529; Novels. / lcgft / http://id.loc.gov/authorities/genreForms/gf2015026020; Science fiction. / fast / http://id.worldcat.org/fast/1726489; Novels. / fast / http://id.worldcat.org/fast/1921742; Fiction. / fast / http://id.worldcat.org/fast/1423787